Determinants of Employee Performance Through Management Decision Making at PT. Air Liquide Indonesia - Sri Wahono; Hapzi Ali; Tri Widyastuti (Dinasti International Journal of Economics, Finance & Accounting, 2023)
In order to enhance human resources within the IM Division, all company activities must be aligned with the company's objectives. Effective communication is crucial in achieving these goals and obtaining information to inform decision making. The Brio system is an example of technology acceptance, as it provides data on liquefied gas usage and tank levels to customers. The system must be reliable in sending this data to the distribution department to effectively analyze customer needs. The information gathered through effective communication and technology acceptance through the Brio system can then be utilized as data for making well-informed and low-risk decisions. These two independent variables, communication and technology acceptance, along with decision making as the intervening variable, play a significant role in improving employee performance. They assist management in the process of enhancing employee performance within the company.